The effect of breed and stage of lactation on the microbiological status of raw milk - Petróczki, Flóra Mária; Tonamo, Tema Andualem; Béri, Béla; Peles, Ferenc (Acta Agraria Debreceniensis, 2019)
The microbiological quality of the milk is important not only for food safety, but it can also influence the quality of dairy products. The microbiological status of raw cow milk can be influenced by many factors. Our aim was to determine whether there was a difference between the microbiological quality of milk of two different cow breeds (Holstein Friesian and Jersey) kept and milked in the same conditions, and how the microbiological quality of the raw cow milk changed during lactation (beginning, mid, and end). Samples were taken and analysed in July, August and September in 2018 from two dairy farms in Hajdú-Bihar county. During the conducted studies, the total plate count (TPC), the coliform count, the Staphylococcus aureus count and the coagulase-negative Staphylococcus (CNS) count of raw milk samples were determined.There was no significant difference (P>0.05) between the milk of the Holstein Friesian and Jersey breeds in the case of TPC. However, the mean coliform count of milk samples taken from Holstein Friesian cows was significantly lower (P